Sancto Grisogono quo gaudet Iadra patrono: The Dedicatory Inscription of St Chrysogonus and the Tradition of Martyr’s translatio - Vedriš, Trpimir (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić’s 70th birthday, 2020)
The paper discusses possible implications of the new interpretation of a late-twelfth century inscription in the Romanesque church of St Chrysogonus in Zadar for understanding of the (liturgical and collective) memory of the translation of the relics of St Chrysogonus to Zadar. Departing from the reassessment of the now-lost three inscriptions in the main apse of the monastic church of St Chrysogonus, the aim is to try to shed new light on the beginnings of the veneration of the relics of St Chrysogonus as well as the establishment of late medieval liturgical celebration of the consecration of the same church. Offering a new reading of the dedicatory inscription dated to 1175, the paper moves further offering to contextualize the inscription – interpreted as reflecting some sort of collective memory of the time the relics arrived to Zadar – in the framework of the beginnings of the communal cult of St Chrysogonus in Zadar at the turn of the twelfth to the thirteenth century.